2014
DOI: 10.1212/wnl.0000000000000814
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of TERT , EGFR , and IDH status defines distinct prognostic glioblastoma classes

Abstract: The analysis of TERTp-mut, in combination with EGFR amplification and IDH mutation status, refines the prognostic classification of GBMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
140
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 196 publications
(159 citation statements)
references
References 27 publications
13
140
3
3
Order By: Relevance
“…In the present study, TERT promoter mutations were identified in 64% of GBMs, and were associated with the age and sex of patients with GBM. These results are consistent with those of previous studies (4,5). The association between TERT promoter mutations and other genetic alterations has been observed in previous studies (4,5).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, TERT promoter mutations were identified in 64% of GBMs, and were associated with the age and sex of patients with GBM. These results are consistent with those of previous studies (4,5). The association between TERT promoter mutations and other genetic alterations has been observed in previous studies (4,5).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies demonstrated that the association between telomere length and TERT expression is complex and may be regulated by a number of other factors, including the activities of signaling pathways and alterations of genes (4,28,29). Previous studies have demonstrated that TERT promoter is the most common type of mutation in GBMs, suggesting that it may be an early event in GBM carcinogenesis (2,4,5,(30)(31)(32). In the present study, TERT promoter mutations were identified in 64% of GBMs, and were associated with the age and sex of patients with GBM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not find that the TERT promoter mutation status is an independent prognostic biomarker of primary GBM, even though the TERT mutation status analyses revealed borderline significance in the univariate survival analysis (Figure 3E). However, some GBM studies that included both primary and secondary GBM patients suggested that TERT promoter mutations are independently associated with a negative prognosis 19, 20. We speculate that the prognostic value of TERT promoter mutations in relation to poor survival is partly due to the IDH status.…”
Section: Discussionmentioning
confidence: 81%